(untitled) (Revista Educação, Artes e Inclusão, 2021)
This paper analyzes the academic scientific productions on Art and Special Education available at the IBICT Digital Library of Theses and Dissertations This is a bibliographical research, of quantitative nature, which had the bibliometric analysis resources to collect, treat and analyze all the material. The research result presents the final corpus of 16 articles, produced by 16 different authors, mostly by women, from 2003 to 2017, with a bigger predominance in the quadrennium 2009 to 2012. The studies focus on the Southeast Region and on higher education institutions such as UDESC, USP, UFU, UFRN. Research defended in the Postgraduate Programs in Arts and, generally, with emphasis on Visual Arts was predominant. The themes of the 16 productions focus on the discussion of inclusion in and through Art, followed by Art teaching. The paper’s objectives were the importance of understanding the role of Art in the social and school inclusion of people with disabilities, as well as understanding the relevance of art in formal and non-formal education. The study’s results indicate that Art brings many benefits related to life quality and promotion of inclusion, but few emphasize the pedagogical and formative aspects of Art. It is concluded that scientific production on Art and Special Education is relevant but requires rethinking the appropriation of artistic knowledge and discussion by people with disabilities.